Simone de Beauvoir y la historia de las mujeres. Notas sobre El Segundo Sexo - Rosa María Cid López (Investigaciones Feministas, 2009)
This paper is intended to highlight the role played by Simone de Beauvoir and, to be more precise, by her work The Second Sex, in the period in which the first studies on Women's History were carried out. In particular, it will deal with de Beauvoir's theoretical analyses of the construction of femininity as a social and cultural process, and of the patriarchal image of woman as the other. One of the aims of this paper is that of showing the extent to which concepts such as gender and alterity, even identity, are present in her work; likewise, it is concerned with presenting the mechanisms that legitimate a certain social order, i.e. the patriarchal model, and, more specifically, with explaining what gave rise to those mechanisms, and how the identification of women with the weak gender guaranteed their continuity.